Zeil Neelson and Wade-Fite stains to demonstrate medlar bodies of chromoblastomycosis - Lokuhetty, M. D. S.; Alahakoon, V S; Kularatne, B D M U; De Silva, M.V.C. (Wiley-Blackwell Publishing Ltd., 2007)
To the Editor, The characteristic fungal bodies of chromoblastomycosis, known as Medlar bodies, are visualized as golden brown rounded bodies in routine hematoxylin and eosin (H&E) stained tissue sections of the skin (Fig. 1). We report a hither to undocumented staining pattern of Medlar bodies that will be useful when they are not identified in routine H&E stains, in cases with a high index of clinical suspicion. Chromoblastomycosis is a chronic fungal infection of skin and subcutaneous tissue seen in rural populations of tropical and subtropical regions. The commonly reported causative fungi are Fonsecaea pedrosoi, Phialophora verrucosa and Cladosporium carrionii. 1 The organisms after gaining entry to the body through traumatic skin injury produce a slow growing verrucous nodule or a plaque.2 The histological diagnosis of the disease is by staining tissue sections of skin with the H&E stain to demonstrate Medlar bodies.3,4 A 72-year-old female presented with a non-itchy warty growth on the dorsum of the left foot of oneyear duration. The warty growth had a hyperkeratotic center with peripheral scarring. The clinical differential diagnosis in this patient included warty tuberculosis and chromoblastomycosis. H&E-stained sections of the lesion showed epidermal hyperplasia and a dense chronic inflammatory infiltrate with illformed granulomata within the dermis. Although these histological features supported a diagnosis of chromoblastomycosis, the characteristic Medlar bodies were not seen. Therefore, the Zeil Neelson stain (ZNS) was performed to rule out the possibility of warty tuberculosis. In the ZNS sections, Medlar bodies were seen prominently as dark grayish oval bodies against a light blue background (Fig. 2). Subsequently, ZNS was performed on tissue sections of three confirmed cases of chromoblastomycosis retrieved from the departmental case files. A similar pattern of staining was seen in all three cases confirming that Medlar bodies of chromoblastomycosis are stained by the ZNS, traditionally used to demonstrate acid fast bacilli. Following this, Wade-Fite staining (WFS) was done on tissue sections in the above patients. Medlar bodies stained positively with WFS in a pattern similar to that seen with the ZNS (Fig. 3). Medlar bodies were easier to identify in the ZNS and WFS than in the routine H&E-stained slides as all inflammatory cells and the back ground stained Fig. 1. Fig. 2. J Cutan Pathol 2007: 34: 71–72 Blackwell Munksgaard. Printed in Singapore Copyright # Blackwell Munksgaard 2006 Journal of Cutaneous Pathology 71 in a uniform light blue color, enhancing the detection of dark grayish blue Medlar bodies (Figs 2, 3). When compared with the traditional special stains used to demonstrate Medlar bodies (such as PAS and silver methenamine), ZNS and WFS are easier stains to perform than the silver methenamine stain but requires a longer duration of time than the PAS stain. The reason, the Medlar bodies were seen in the ZNS and not in the H&E stain in the initial patient, could have been due to the inflammatory infiltrate making it difficult to detect the Medlar bodies. There is a possibility that Medlar bodies could have made their appearance in the deeper sections done for ZNS, although adequate number of deeper sections had already been examined. We conclude that the ZNS and WAS are useful stains in suspected chromoblastomycosis when Medlar bodies are not seen in routine H&E-stained sections. Acknowledgements We thank S. Y. Shriani, technical officer in our department, for performing these stains. MDS Lokuhetty VS Alahakoon BDMU Kularatne MVC De Silva Department of Pathology, Faculty of Medicine, University of Colombo, Colombo, Sri Lanka email: alaha@visualnet.lk References 1. Sharma NL, Sharma RC, Grover PS, et al. Chromoblastomycosis in India. Int J Dermatol 1999; 38: 846. 2. Rubin HA, Bruce S, Rosen T, et al. Evidence of percutaneous inoculation as the mode of transmission for chromoblastomycosis. J Am Acad Dermatol 1991; 25: 951. 3. Bonifaz A, Carrasco-Gerard E, Saul A. Chromoblastomycosis: clinical andmycologic experience of 51 cases. Mycoses 2001; 44: 1. 4. McGinnis MR. Chromoblastomycosis and phaeohymphomycosis: new concepts, diagnosis and mycology. J Am Acad Dermatol 1983; 8: 1 Fig. 3. Letter to the Editor 72